MONITORING OF THE ANKLE REHABILITATION USING PLANTAR FORCE TYPE SENSOR - Sharad Pawar1,Umesh Dudbhate2, Shailaja Patil3 (International Journal of Innovations in Engineering Research and Technology, 2022)
Ankle injuries are one of the most common types of athletic injuries and can have lasting adverse effects on daily life as well as athletic performance without proper rehabilitation and in severe cases can result in chronic ankle instability. Physiotherapy while effective, still employs many techniques that are largely qualitative for lack of an easily accessible system that can offer a quantitative approach. The design of an ankle rehabilitation monitor seeks to provide a fast, effective, affordable and repeatable method of acquiring qualitative data of importance when diagnosing and treating injuries related to the ankle. Plantar forces acting on the sole of the foot represent a set of data that can be important to a practitioner but are difficult to acquire without specialized equipment, and as such are part of the focus in the design of an ankle rehabilitation monitor. The device strives to provide a physiotherapist with plantar force measurements using a set of force sensing resistors affixed to a shoe insert that can be retained and compared in order to track the rehabilitation of ankle related injury. A proof of concept utilizing three such resistors is implemented and demonstrates that this approach is a reasonable design. The theory behind the device and its hardware and software design, experimental results, and efficacy are presented within.